The Role of Leadership on Employees’ Satisfaction and Retention After the Covid-19 Pandemic: A Case Study of Hotel Industry in Pakistan - Amjad, Muhammad Farhan (2025)
This study examines the critical role of leadership in shaping employee satisfaction and retention within Pakistan's hospitality sector during the post COVID 19 recovery period. The pandemic created unprecedented operational challenges, underscoring the necessity for adaptive leadership and robust organizational support systems to maintain workforce stability. The research specifically analyzes how crisis leadership competencies influence employee outcomes, with organizational support mechanisms including flexible work arrangements and professional development programs serving as key mediating factors. Utilizing a quantitative methodology, structured surveys were administered to hotel employees across various organizational levels and geographic locations in Pakistan. Employee satisfaction was assessed using the Minnesota Satisfaction Questionnaire, while turnover intentions were measured through the Turnover Intention Scale. Advanced statistical analysis revealed significant positive correlations between effective crisis leadership and employee satisfaction, with organizational support demonstrating substantial mediating effects. The findings highlight that hospitality organizations combining strong crisis leadership with comprehensive support frameworks achieve higher workforce retention and engagement levels. This research contributes to academic discourse by integrating leadership and organizational support theories within Pakistan's unique hospitality context, while offering practical insights for industry practitioners. Key recommendations include investing in crisis leadership training programs and implementing evidence based support policies to enhance employee wellbeing and organizational resilience. The study provides contemporary perspectives on improving workforce stability in turbulent environments, ultimately emphasizing the interdependent relationship between leadership, organizational support, and sustainable employee outcomes.